The relationship between stress levels and the habits of consuming high-sugar food among undergraduate students - 'Azizah, Zulfa; Putriana, Dittasari; Dewi, Agil Dhiemitra Aulia (Jurnal Cakrawala Promkes, 2025)
The SKI 2023 survey revealed that 81% of students consume foods high in sugar, while a preliminary study found that severe academic stress increases by 34.2% among students aged 21 to 25. High-sugar food consumption is believed to help reduce stress temporarily. This study aims to investigate the relationship between stress levels and the consumption of high-sugar foods among students at Universitas 'Aisyiyah Yogyakarta (UNISA). This analytical observational research employed a cross-sectional design. The sample consisted of 168 students aged 18 to 25 who were selected using purposive sampling. Data were obtained through the UNISA-UiTM (Universitas 'Aisyiyah Yogyakarta and Universitas Teknologi MARA) 2023 Mental Health research. Respondent characteristics were collected using a structured questionnaire, high-sugar food consumption habits were assessed using the Q-FFQ, and stress levels were measured with the DASS questionnaire. Data collection was conducted both online and offline. Spearman rank correlation analysis was performed, with a significance threshold of p < 0.05. The findings revealed that 39.2% of students experienced stress, while 52.98% had a habit of consuming high-sugar foods. However, the analysis showed no statistically significant relationship between stress levels and high-sugar food consumption (p = 0.11). While no direct correlation was established, high-sugar food consumption remains a concern due to its potential health impacts. Students are encouraged to adopt healthier dietary habits by monitoring their sugar intake, reading nutritional labels, and limiting high-sugar foods to 1–3 times per week. Promoting awareness of balanced diets and stress management techniques may help improve students' mental and physical well-being.